Book Reviews (The Muslim world, 1995)
Book Reviewed in This Article: Maulana Azad. By Khaliq Ahmad Nizami The Renewal of Islamic Law: Mu ammad Baqer as- adr. Najaf and the Sh?'i International. By Chibli Mallat The Arab Christian: A History in the Middle East. By Kenneth Cragg Faith and Practice of Islam: Three Thirteenth Century Sufi texts. The Tao of Islam: A Sourcebook on Gender Relationships in Islamic Thought. By Sachiko Murata A World of Difference: Islam and Gender Hierarchy in Turkey. By Julie Marcus Oil Monarchies: Domestic and Security Challenges in the Arab Gulf States By F. Gregory Gause A mad ibn Naq?b al-Misr? Approaches to the Qur'ān. Edited by G. R. Hawting and Abdul-Kader A. Shareef Palestinians The Making of a People. By Baruch Kimmerling & Joel S. Migdal